A repeated cross-sectional survey assessing university students' stress, depression, anxiety, and suicidality in the early stages of the COVID-19 pandemic in Poland. Issue 15 (2nd November 2022) - Debowska, Agata; Horeczy, Beata; Boduszek, Daniel; Dolinski, Dariusz
Abstract: Background: The time of widespread outbreaks of infectious diseases can lead to elevated stress and mental health problems among all persons affected, and in particular those sub-groups of the population that are at an increased risk of mental health problems. One such vulnerable group constitutes university students. The aim of this study is to assess stress, depression, anxiety, and suicidality among different groups of university students (medical, psychology, and other). Methods: Using a repeated cross-sectional study design, we collected survey data among a large sample of 7228 university students from Poland (mean age = 22.78, s.d. = 4.40; 81% female). Data were collected in five waves, during the first 2 months of the COVID-19 pandemic in Europe (March and April 2020). Results: The results demonstrate a significant increase in depression levels as the pandemic was progressing. We also found that female students scored significantly higher than male students on depression, anxiety, and stress. Psychology students recorded the lowest scores on depression and anxiety. Young adult students (aged 18–24 years) had more symptoms of depression, anxiety, and suicidality than adult students (⩾25 years). Conclusions: These results provide insights into stress and mental health among university students during the early stages of the COVID-19 pandemic. Findings can be used for a more effective identification of students who may struggle during next stages of the pandemic and future crises.